Answer: No solution
<u>Step-by-step explanation:</u>
x - 3y = 2 → x = 3y + 2
2x - 6y = 6
2(3y + 2) - 6y = 6 <em>substituted x with 3y+2</em>
6y + 4 - 6y = 6 <em>distributed 2 into 3y+2</em>
4 = 6 <em>simplified (6y - 6y = 0)</em>
4 = 6 is a FALSE statement so there is NO SOLUTION
Answer:
3 2/3
Step-by-step explanation:
To do this question, you would need to multiply 7 1/3 with 1/2. The answer is 3 2/3.
Triangle a - acute
Triangle b - acute
Triangle c - acute
Triangle d - right
Answer:
I
Step-by-step explanation:
This is a dotted line so we can automatically eliminate, b, e, g, h, and j. The shading in greater than, so we can eliminate a, and d.
Now all we have left are c, f and *i,
*(because if converted to y intercept the sign will flip because the y is negative in this equation.)
Now convert to y intercept form (y=mx+b).
Flip the sign because some are negative.
C. y>(-5/2)x+0
F. y>-2x+9
I. y>(4/3)x-(5/3)
Now use rise over run, or you could just look at the b. B is equal to the y-intercept. It can't be 0 or 9, and (-5/3) is equal to -1.67. So isn't that the closest to what the y intercept looks like in the graph?
100/10=10
Michelle used 10 dimes because a dime is worth 10 cents, a dollar is 100 cents, 10 dimes is equal to 100 cents.